Think and cope positively: A feasibility and acceptability study to improve the subjective well-being of people affected by a severe mental disorder - Caballero Campillo, Rocío; Peinado, Vanesa; Valiente Ots, Carmen; Vucic Sánchez, Ana María; Alonso Cristobo, Álvaro Jesús; Caperos Montalbán, José Manuel (My University, 2025)
El estudio evalúa la viabilidad y aceptabilidad de Think and Cope Positively, un programa estructurado de 15 sesiones orientado a mejorar el bienestar subjetivo de personas con trastorno mental grave. Participaron 26 personas derivadas de servicios de salud mental, de las cuales 20 completaron la intervención. Se analizaron asistencia, cumplimiento del protocolo, implicación en tareas y satisfacción, así como cambios en bienestar hedónico y eudaimónico, optimismo, alianza terapéutica y sintomatología psicológica antes y después del programa. Los resultados muestran alta satisfacción y adherencia, junto con mejoras significativas en bienestar, optimismo y vinculación terapéutica, y reducciones en varios síntomas clínicos. El programa se presenta como una intervención factible, segura y prometedora dentro de la rehabilitación psicosocial.

This study evaluated the feasibility and acceptability of Think and Cope Positively, a structured 15-session program aimed at enhancing subjective well-being among adults diagnosed with severe mental disorders. Twenty-six participants were recruited through mental health services, and feasibility indicators—including attendance, protocol adherence, and satisfaction—were assessed together with pre-post measures of hedonic and eudaimonic well-being, optimism, therapeutic alliance, and psychological symptoms. Of the 26 participants, 20 completed the program, demonstrating high adherence and satisfaction. Significant improvements were found in well-being, optimism, and therapeutic engagement, alongside reductions in several clinical symptoms. Findings suggest that the program is a feasible, acceptable, and safe psychosocial intervention that may enhance well-being in individuals with severe mental health conditions.
Artículos en revistas